The Effectiveness of a Blended Program in Enhancing Creative Journal Writing among Palestinian Secondary School Students - Myassar Khalil Abu Ghlasi (Ain Shams University, 2023)
This study aims at investigating the effectiveness of a blended program in enhancing journal writing among Palestinian secondary school students. The sample of the study consisted of 36 female students as an experimental group. A blended program was used for teaching the group. The researcher chose journal writing as one of the creative writing strategies to be treated in this study. A pre-posttest was used to measure the effectiveness of the program on students' achievement of the experimental group in journal writing. Data were analyzed using descriptive statistics such as means and standard deviations, in addition to the analysis of covariance (ANCOVA). The main results of the study indicated that the mean scores of the experimental group were significantly high. This means that the use of the blended program had a significantly greater positive effect on the students' achievement in journal writing in favor of the posttest and showed also significant results in all journal writing sub-skills.